Optimization of Local Commodity Distribution Through Sea Toll Program: An Evaluative Study of the Port-To-Port System of Tenau Kupang Port as a Regional Hub in East Nusa Tenggara - Antonius Leonardo Antjak; Putri Dwi Kinanti Djahamouw; Dian Erlina Wati Johannis (Jurnal Impresi Indonesia, 2025)
This research aims to analyze the effectiveness of the Sea Toll system in supporting local commodity distribution and to assess the role of Tenau Kupang Port as a regional hub in East Nusa Tenggara Province (NTT). It employs a mixed-methods approach with quantitative-descriptive and explanatory designs, drawing on secondary data from KSOP Kupang and BPS NTT for 2023–2024. The analysis incorporates descriptive statistics, multiple linear regression, load factor analysis, total logistic cost (TLC), and quantitative SWOT. The results show that the Sea Toll system in NTT has achieved physical accessibility through regular inter-island connectivity but has not achieved functional accessibility due to low return loads, with the average load factor reaching only 24%. Regression analysis indicates that shipping frequency and return cargo volume have a significant effect on distribution effectiveness, while logistics costs and travel time exert a moderate positive influence. The Sea Toll Program reduces average logistics costs by 31% compared to conventional modes. The SWOT analysis yields an internal factor value of 2.09 and an external factor value of 2.56, placing Tenau Kupang Port in the growth strategy quadrant. This study concludes that the Sea Toll system is physically effective but not economically efficient. Strengthening the function of Tenau Kupang Port as a regional hub—through consolidation of local cargo, cold storage facilities, land-sea mode integration, and digitalization of logistics systems—represents a strategic step toward sustainable maritime logistics efficiency in Eastern Indonesia.